(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Streptococcus pneumonia is a common pathogen of pneumonia, bacteremia, and meningitis in children. Of which, invasive diseases caused by Streptococcus pneumoniae contributes to the increasing rate of morbidity and mortality, especically children younger than 5 years old. Is there difference between pneumococcal pneumonia and invasive pneumococcal disease? Objectives: The characteristics of children with invasive diseases caused by streptococcus pneumonia in Children’s Hospital 1. Methods: This research is a case series study in which disease cases are retrospectively recruited from January 2017 to July, 2022 and prospectively from July, 2022 to July, 2023. Results: Of the researched population, there are 76,8% of children aged <60 months with male/ female rate is 1,3/1. The number of children without having prior pneumococcal vaccination is 57,6%. Additionally, 75,8% of children are precedingly given antibiotic pre-hospitalization, of which, the most commonly used one is amoxicillin ± clavulanic acid (44%). Common signs and symptoms are fever (94,9%), cough (96%), rhinorrhea (71,7%), dyspnea (40,4%), wheezing (13,1%), chest pain (8%), crackles (80,8%), tachypnea (79,8%), subcostal retraction (72,7%), pleural effustion (18,2%), consolidation (7,1%). Most children have leukocytosis (74,7%), high CRP level >20mg/L (84,8%), anemia (56,1%), lobar pneumonia on X-ray (34,3%). Pneumococci is detected in blood in 81,8% while the figure for pleural fluid is modestly 10,1%. Common complications are pleural effusion (43,5%) and necrotizing pneumonia (19,2%). In our study, pneumococci is highly sensitive to vancomycin (100%), levofloxacin (88,9%), linezolid (100%). Invasive pneumococci have a high rate of resistance to macrolid (100%), sulfamid (77,8%), penicillin (20,2%). Most commonly used antibiotics during hospitalization are Cephalosporin 3rd generation. There are 96% of patients with improvement and recovery, while the mortality rate is 2%. Conclusions: Invasive pneumococcal pneumonia should be considered situations including clinical or laboratory complications, high fever with difficult breathing and poor feeding, or cases with high CRP level (> 100) with associated anemia.